2014
DOI: 10.1016/j.nuclphysb.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetry breaking by higher dimension operators

Abstract: We discuss a supersymmetry breaking mechanism for N=1 theories triggered by higher dimensional operators. We consider such operators for real linear and chiral spinor superfields that break supersymmetry and reduce to the Volkov–Akulov action. We also consider supersymmetry breaking induced by a higher dimensional operator of a nonminimal scalar (complex linear) multiplet. The latter differs from the standard chiral multiplet in its auxiliary sector, which contains, in addition to the complex scalar auxiliary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…In addition, the theory (55) has been studied in Refs. [22,23], where now the general functions in the higher derivative gauge sector are fixed by the form of the integrated out L 0 . The component form reads (after rescaling V → 2V )…”
Section: Corrections In New-minimal Supergravitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the theory (55) has been studied in Refs. [22,23], where now the general functions in the higher derivative gauge sector are fixed by the form of the integrated out L 0 . The component form reads (after rescaling V → 2V )…”
Section: Corrections In New-minimal Supergravitymentioning
confidence: 99%
“…To study the implications of the corrections on the inflaton potential we look again at the minimum C =C = b = 0 with the redefinition (22). The inflaton field φ will now have a potential …”
Section: Corrections In Old-minimal Supergravitymentioning
confidence: 99%
“…First, we have studied only chiral and vector superfields as the source of supersymmetry breaking, which does not exhaust all the possibilities. It is known, for example, that supersymmetry breaking can be sourced also by linear superfields [52][53][54]. One could then investigate what are the general properties of this other class of models, in the spirit of the presentation we gave in this work.…”
Section: Jhep08(2017)117mentioning
confidence: 97%
“…This model has been studied in [8][9][10] where it has been demonstrated that the equations of motions have several vacuum solutions including one which breaks supersymmetry. For that reason it would be interesting to find the supercurrents for this theory and the list of supergravities it can be coupled to.…”
Section: Jhep02(2017)076mentioning
confidence: 99%
“…It has recently become clear that this is not the case since in certain theories with higher derivative terms some of the auxiliary components can become propagating and thus change the degrees of freedom of the theory. This fact motivated the use of complex linear superfield as a prime candidate for various phenomenological models regarding spontaneous supersymmetry breaking [6][7][8][9][10][11] that is, so far, much less understood than the standard mechanisms. For that reason it would be desirable to study aspects of theories of complex linear superfields.…”
Section: Introductionmentioning
confidence: 99%